(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
As a result of challenges associated with swallowing, there has been a recent uptick in thedemand for tablets that may be dissolved in the mouth. This trend has been observed particularly amongelderly and juvenile patients. Cinnarizine, an H1-receptor antagonist, is a common medication fortreating motion sickness, vomiting, and vertigo. Cinnarizine tablets that dissolve in the mouth were madeusing effervescent, superdisintegrant addition, and sublimation processes respectively. Since theSuperdisintegrant addition method resulted in the quickest disintegration time, it was selected for furtherstudy. For the next nine batches, we diluted model drug, carboxymethylcellulose salt, and L-HPC tovarious concentrations (B1-B9) The range of strengths covered was from 5 to 10.It was determinedhow much each formulation varied in weight, how hard it was, how friable it was, how much activeingredient it contained, how long it took to disintegrate in vitro, how long it took to wet in vitro, and howwell it dissolved in vitro. The formulation that contained 10 L-HPC exhibited a shorter disintegrationtime of 25.3 seconds and a shorter wetting time (29.1 seconds). In-vitro dissolving tests demonstratedthat the whole dose of medication was released within just six minutes.